2015
DOI: 10.1539/joh.15-0111-oa
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of workplace violence against clinical physicians in hospitals

Abstract: Determinants of workplace violence against clinical physicians in hospitals: Jeng‐Cheng Wu, et al. Department of Urology, Taipei Medical University Hospital, Taiwan Objective Workplace violence in the health sector is a worldwide concern. Physicians play an essential role in health‐care teamwork; thus, understanding how organizational factors influence workplace violence against physicians is critical. Methods A total of 189 physicians from three public hospitals and one private hospital in Northern Taiwan com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 28 publications
8
36
3
10
Order By: Relevance
“…Job demands, often considered a proxy for work stress, 47 were significantly associated with violent threats towards physicians in a Taiwanese study, 24 which supports findings in the current study. However, in that study, safety climate ratings were also significantly protective of threats, whereas in our study, work stress was only significant before the safety climate variable was added to the model for verbal violence.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Job demands, often considered a proxy for work stress, 47 were significantly associated with violent threats towards physicians in a Taiwanese study, 24 which supports findings in the current study. However, in that study, safety climate ratings were also significantly protective of threats, whereas in our study, work stress was only significant before the safety climate variable was added to the model for verbal violence.…”
Section: Resultssupporting
confidence: 88%
“…24-25 In a Taiwanese study of physicians from four hospitals, lower safety climate ratings, along with higher job demands, were associated with workplace violence. 24 Although that study distinguished between violent threats and sexual harassment, violent threats were defined as any verbal or physical violence, and thus did not distinguish between the two when examining safety climate determinants. A study from a single Israeli hospital found that enhancing the safety climate via a three-day educational program helped to decrease the number of aggressive incidents towards staff on closed psychiatric wards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job demands. Five items of a Chinese version [35] of the Job Content Questionnaire [36], with five response categories ranging from 1 (strongly disagree) to 5 (strongly agree), were used to measure the job demands physicians experienced. Items were slightly modified to be applicable to the health care context when needed.…”
Section: Methodsmentioning
confidence: 99%
“…24 Birçok çalışmada, çalışmamıza benzer şekilde sözel ve fiziksel şiddet en sık acil kliniği çalışanları karşı gerçekleşmiştir. 25,26 Bunun sebebi acil kliniklerinin yoğun olması; başvuran vakaların çeşitliliği ve genel olarak acilde stres seviyesinin yüksek olması olabilir.…”
Section: şEkil 2 şIddetin Meydana Geldiği Hastane Bölümleriunclassified